Charmed baryon weak decays with SU(3) flavor symmetry. (November 2017) - Geng, C.; Hsiao, Y.; Liu, Chia-Wei; Tsai, Tien-Hsueh
Abstract We study the semileptonic and non-leptonic charmed baryon decays with SU(3) flavor symmetry, where the charmed baryons can beB c = (Ξc 0, Ξc +, Λc + ), B c ′ = (Σ c (++, +, 0), Ξc ′ (+, 0), Ωc 0 ), B cc = (Ξcc + +, Ξcc +, Ωc + ) or B cc = Ωccc + + . WithB n (′) denoted as the baryon octet (decuplet), we find that theB c → B n ′ ℓ + ν ℓ decays are forbidden, while the Ωc 0 → Ω− ℓ + ν ℓ, Ωcc + → Ωc 0 ℓ + ν ℓ, and Ωccc + + → Ωcc + ℓ + ν ℓ decays are the only existing Cabibbo- allowed modes forB c ′ → B n ′ ℓ + ν ℓ, B cc → B c ′ ℓ + ν ℓ, and B ccc → B cc (′) ℓ + ν ℓ, respectively. We predict the rarely studiedB c → B n (′) M decays, such as ℬ Ξ c 0 → Λ 0 K ¯ 0, Ξ c + → Ξ 0 π + = 8.3 ± 0.9, 8.0 ± 4.1 × 10 − 3 and ℬ Λ c + → Δ + + π −, Ξ c 0 → Ω − K + = 5.5 ± 1.3, 4.8 ± 0.5 × 10 − 3 $$ \mathrm{\mathcal{B}}\left(Ξ_c^0→ Λ^0{\overline{K}}^0, Ξ_c^{+}→ Ξ^0π^{+}\right)=\left(8.3± 0.9, \ 8.0± 4.1\right)× {10}^{-3}\kern0.5em and\kern0.5em \mathrm{\mathcal{B}}\left(Λ_c^{+}→ Δ^{++}{π}^{-}, Ξ_c^0→ Ω^{-}{K}^{+}\right)=\left(5.5± 1.3, \kern0.5em 4.8± 0.5\right)× {10}^{-3} $$ . For the observation, the doubly and triply charmed baryon decays of Ω cc + → Ξ c + K ¯ 0, Ξ cc + + → Ξ c + π +, Σ c + + K ¯ 0, and Ω c c c + + → Ξ cc + + K ¯ 0, Ω cc + π +, Ξ c + D + $$ Ω_{cc}^{+}→ Ξ_c^{+}{\overline{K}}^0, Ξ_{cc}^{++}→ \left(Ξ_c^{+}{π}^{+}, {\varSigma}_c^{++}{\overline{K}}^0\right), \kern0.5em and\kern0.5em Ω_{ccc}^{++}→ \left(Ξ_{cc}^{++}{\overline{K}}^0, Ω_{cc}^{+}{π}^{+}, Ξ_c^{+}{D}^{+}\right) $$ are the favored Cabibbo-allowed decays, which are accessible to the BESIII and LHCb experiments.